Zuhud, Sebuah laku Tasawuf untuk Tazkiyah Peradaban Akuntansi - Ali Farhan (Akuntansi : Jurnal Akuntansi Integratif, 2020)
This study aims to reconstruct modern accounting with the postmodernism paradigm and Zuhud as a decosntructive analysis approach. Based on the results of the analysis, the practice of accounting must return to the divine values; to force Allah subhana wa ta'ala, to carry out his commands and stay away from his prohibitions, also to make Allah subhana wa ta'ala as the goal of life.